The Effect of Strengthening (Reinforcement) and Confidence on the Skills of Passing Techniques in Volleyball Games at SMA Negeri 6 Padangsidimpuan City - Asman Rafsanjani Daulay; Sanusi Hasibuan; Ibrahim Ibrahim; Indra Kasih (RIRAI Publisher, 2023)
The purpose of this study was to determine positive and negative reinforcement on students' passing skills and self-confidence. The design used in this study is a 2x2 factorial. The 96 students who met the requirements were divided into four groups using the matching pairing technique so that each group had 24 samples. The results of this study are: 1. In this study it was found that Fh = 8.82 and Ft at dk (3.24) = 3.10, from this calculation it can be concluded that Fh > Ft means that there is a significant difference between reinforcement ) positive and negative reinforcement of basic volleyball technical skills. 2. In this study it was found that Fh = 188.41 and Ft at dk (3.24) = 3.10, from these calculations it can be concluded that Fh > Ft. it can be concluded that there is an interaction between reinforcement and confidence in the basic technical skills of volleyball. 3. Calculation of the tukey test in the study with a comparison of A1B1 and A2B1, it is obtained that Qh = 23.19 and Qt (2:48) = 3.20. So it can be concluded that Qh > Qt. This means that there is a significant difference between positive reinforcement and negative reinforcement on the basic volleyball game technical skills for students with high self-confidence. 4. The calculation of the tukey test in the study with a comparison of A2B2 and A2B2, it is obtained that Qh = 15.60 and Qt (2:48) = 3.20. So it can be concluded that Qh > Qt. This means that there is a significant difference between positive reinforcement and negative reinforcement on the basic volleyball game technical skills for students with low self-esteem.